Pelaksanaan Wajib Notifikasi (WiFi) TB di Dinas Kesehatan Kabupaten Jember - Fiya Wadudah; Irma Prasetyowati; Candra Bumi (Pustaka Kesehatan, 2023)
Indonesia will follow the global elimination target, is the elimination of TB in 2035 and Indonesia to be free of TB in 2050. The challenge in the Tuberculosis control program in Indonesia is there are many undetected cases of tuberculosis and cases that have undetected and unreported. So, needs to change the case-finding approach from passive to intensive and active. The complexity of filling out TB forms by private doctors has resulted in the low notification of TB patients. So, I made an electronic system using a smartphone-based application, namely the Application Mandatory Notification (WiFi) of TB, which application is made simpler and easier. This study aims to describe the implementation of compulsory TB notification (WiFi) in the Public Health Office Jember District. This research uses descriptive research. The research sample was 2 TB officers. This research was analyzed using descriptive analysis. The results of this study indicate the description of the input, process, and output aspects of the implementation of mandatory notification (WiFi) TB.